Core–Shell Double Gyroid Structure Formed by Linear ABC Terpolymer Thin Films. Issue 9 (26th March 2018) - Antoine, Ségolène; Aissou, Karim; Mumtaz, Muhammad; Telitel, Siham; Pécastaings, Gilles; Wirotius, Anne‐Laure; Brochon, Cyril; Cloutet, Eric; Fleury, Guillaume; Hadziioannou, Georges
Abstract: The synthesis and self‐assembly in thin‐film configuration of linear ABC triblock terpolymer chains consisting of polystyrene (PS), poly(2‐vinylpyridine) (P2VP), and polyisoprene (PI) are described. For that purpose, a hydroxyl‐terminated PS‐ b ‐P2VP (45 kg mol −1 ) building block and a carboxyl‐terminated PI (9 kg mol −1 ) are first separately prepared by anionic polymerization, and then are coupled via a Steglich esterification reaction. This quantitative and metal‐free catalyst synthesis route reveals to be very interesting since functionalization and purification steps are straightforward, and well‐defined terpolymers are produced. A solvent vapor annealing (SVA) process is used to promote the self‐assembly of frustrated PS‐ b ‐P2VP‐ b ‐PI chains into a thin‐film core–shell double gyroid ( Q 230, space group: Ia 3 ¯ d ) structure. As terraces are formed within PS‐ b ‐P2VP‐ b ‐PI thin films during the SVA process under a CHCl3 vapor, different plane orientations of the Q 230 structure ((211), (110), (111), and (100)) are observed at the polymer–air interface depending on the film thickness. Abstract : Frustrated PS‐ b ‐P2VP‐ b ‐PI chains, produced by coupling a PS‐ b ‐P2VP‐OH with a carboxyl‐terminated polyisoprene via a Steglich esterification reaction, are self‐assembled into a thin‐film core–shell double gyroid structure. This Q 230 structure exhibits different plane orientations depending on the film thickness.